2022
DOI: 10.1212/wnl.0000000000200953
|View full text |Cite
|
Sign up to set email alerts
|

CSF Alzheimer Disease Biomarkers

Abstract: Background and ObjectivesThis study aimed to examine whether baseline CSF measures of Alzheimer disease (AD)–related pathology are associated with the time to onset of mild cognitive impairment (MCI) and whether these associations differ by age, sex, Apolipoprotein E (ApoE4) status, and proximal (≤7 years) vs distal (>7 years) time to symptom onset.MethodsMeasures of amyloid (Aβ1-42 and Aβ1-40), phospho-tau (ptau181), and total tau (t-tau) were determined from CSF samples obtained at baseline from participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 57 publications
(83 reference statements)
3
12
0
Order By: Relevance
“…Notably, in the current study, higher Aβ 40 levels were also associated with higher temporal WMH volumes among all subjects and the cognitively normal subgroup, though this association was less robust than for p-tau and t-tau. Although altered levels of Aβ 40 are not typically observed in AD, including the preclinical phase (e.g., [ 57 ]), a recent multicenter study reported slightly, but significantly higher levels of Aβ 40 among patients with AD-dementia compared to controls [ 58 ]. Within this context, it has been suggested that increased Aβ 40 may be a marker of elevated overall amyloid production [ 46, 58 ], overall CSF production [ 59 ], or of reduced clearance of peptides from the brain into the CSF [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the current study, higher Aβ 40 levels were also associated with higher temporal WMH volumes among all subjects and the cognitively normal subgroup, though this association was less robust than for p-tau and t-tau. Although altered levels of Aβ 40 are not typically observed in AD, including the preclinical phase (e.g., [ 57 ]), a recent multicenter study reported slightly, but significantly higher levels of Aβ 40 among patients with AD-dementia compared to controls [ 58 ]. Within this context, it has been suggested that increased Aβ 40 may be a marker of elevated overall amyloid production [ 46, 58 ], overall CSF production [ 59 ], or of reduced clearance of peptides from the brain into the CSF [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were aliquoted into polypropylene cryotubes that were kept on dry ice and immediately transferred to a –80°C freezer for long‐term storage. Samples were thawed for the first time since collection to measure Aβ 40 , Aβ 42 , p‐tau 181 , and t‐tau using fully automated electrochemiluminescence assays (Lumipulse G1200 platform; Fujirebio Diagnostics, Inc.; for coefficients of variation, see Greenberg et al 11 …”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Furthermore, we explored interactions with sex, because prior studies have reported sex-related differences in AD biomarkers [6][7][8] and clinical outcomes. [9][10][11][12] Finally, given the sizeable number of individuals who progressed to mild cognitive impairment (MCI) or dementia (n = 94) during followup, we examined whether CSF biomarker trajectories differed with respect to clinical outcomes. The focus on middle-aged individuals is particularly important because AD pathology begins to develop in midlife, 5,13 and abnormal midlife levels of CSF amyloid and tau are associated with poorer cognitive outcomes.…”
Section: Research In Contextmentioning
confidence: 99%
See 2 more Smart Citations